2021
DOI: 10.37479/jeej.v3i2.10446
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pendidikan Kewirausahaan Dan Motivasi Terhadap Minat Berwirausaha Mahasiswa

Abstract: Penelitian ini bertujuan untuk mengetahui faktor pendidikan kewirausahaan (X1), motivasi (X2) berpengaruh terhadap minat usaha (Y) pada mahasiswa Program Studi Ekonomi Hindu Sekolah Tinggi Agama Hindu Negeri Gde Pudja Mataram. Jenis penelitian ini adalah penelitian asosiatif kuantitatif yang menganalisis hubungan atau pengaruh satu variabel atau lebih terhadap variabel lain. Hasil penelitian menunjukkan bahwa Pendidikan Kewirausahaan (X1) dan Motivasi (X2) berpengaruh signifikan secara parsial dan simultan ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
1
Order By: Relevance
“…0.007 is smaller than 0.050, so X1 impacts students' interest in entrepreneurship, and the fifth hypothesis is rejected. These findings are by research results of Wijaya (2021), Saputra (2021), Hudaya et al (2023), Melinda et al (2023), which found that entrepreneurship-based education and learning can directly influence students' willingness to pursue a career. Become entrepreneurs.…”
Section: Resultsmentioning
confidence: 67%
“…0.007 is smaller than 0.050, so X1 impacts students' interest in entrepreneurship, and the fifth hypothesis is rejected. These findings are by research results of Wijaya (2021), Saputra (2021), Hudaya et al (2023), Melinda et al (2023), which found that entrepreneurship-based education and learning can directly influence students' willingness to pursue a career. Become entrepreneurs.…”
Section: Resultsmentioning
confidence: 67%
“…Because it requires students to use their knowledge, edupreneurship can increase students on the interest in entrepreneurship (Purwanto, 2016). The future skills development of students can be assisted through edupreneurship (Atmaja & Magunani, 2016).…”
Section: The Effect Of the Methods Of Edupreneurship Practice-based B...mentioning
confidence: 99%
“…Profesi sebagian besar dari anggota kelompok usaha Satya Rahayu adalah pedagang, pembuat kue/jajan, penjual canang dan perlengkapan persembahyangan. Untuk dapat bersaing dalam dunia usaha jiwa kewirausahan sangat penting untuk dimiliki oleh para pelaku usaha (Wijaya, 2021).…”
Section: Pendahuluanunclassified